Upgrading of Bio-oils from the Fast Pyrolysis of Longan Wood over the Low Cost Catalysts in a Fluidized Bed Reactor - Paenpong, Chaturong; Chunluang, Weerapun; Pratoomchai, Niwat (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018DO - 10.14456/nujst.2018.26, 2018)
The objective of this work was to upgrade the properties of bio-oil from fast pyrolysis of longan wood by using a low cost catalyst bed material in the fluidized bed reactor. The experiments in this work were performed in two sets. This first one was studied the effects of pyrolysis temperature on the product yield and properties of bio-oil in a fluidized bed reactor to determine the optimal conditions for liquid yield. The experiment were carried out at the pyrolysis temperatures of 450, 500 and 550 ºC and sand was used as bed material. The second part was studied the effects of low cost catalyst bed material on the product yields and properties of bio-oil. The experiments were performed at the optimized pyrolysis temperature from the first set of experiments and sand, iron powder and natural zeolite were used as bed materials. The experimental results showed that increasing pyrolysis temperature from 450 - 550 °C reduced bio-oil yield while increasing the gas yields. The optimum pyrolysis temperature for obtaining highest bio-oil yield for longan wood was 450 °C which gave maximum bio-oil yield of 36.09 wt%. However, when considering the effect of a catalyst bed material which pyrolysis was performed at optimum temperature of 450°C. It was found that the natural zeolite bed gave the highest bio-oil yield of 36.09 wt%. When considering the effect of the catalyst bed materials on bio-oil properties, the sand bed gave the highest pH value (less acidic) and the lowest flash point in comparison with the iron powder and natural zeolite bed. While the bio-oil obtained from natural zeolite bed had the highest higher heating value (HHV) when compared with the sand bed and iron powder bed which the higher heating value of natural zeolite bed is about 2 time of typical bio-oil. Therefore, the term upgrading of bio-oils refers to increasing of heating value and reducing acidic when comparison typical bio-oil. Keywords: Pyrolysis temperature, Fast pyrolysis, Bed materials, Longan wood pruning, fluidized-bed Reactor